Evaluation of new robust silk fibroin hydrogels for posterior scleral reinforcement in rabbits - Xu, Yule; Chen, Qiaolin; Shao, Zhengzhong; Wei, Jiahong; Zhu, Xuyou; Rong, Ao; Chen, Xin; Ni, Yusu; Jiang, Yi (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Currently, there is no ideal material available for posterior scleral reinforcement (PSR) to prevent the progression of high myopia. In this study, we investigated robust regenerated silk fibroin (RSF) hydrogels as potential grafts for PSR in animal experiments to evaluate their safety and biological reactions. Methods: PSR surgery was performed on the right eye of twenty-eight adult New Zealand white rabbits, with the left eye serving as a self-control. Ten rabbits were observed for 3 months, while 18 rabbits were observed for 6 months. The rabbits were evaluated using intraocular pressure (IOP), anterior segment and fundus photography, A- and B-ultrasound, optical coherence tomography (OCT), histology, and biomechanical tests. Results: No complications such as significant IOP fluctuation, anterior chamber inflammation, vitreous opacity, retinal lesion, infection, or material exposure were observed. Furthermore, no evidence of pathological changes in the optic nerve and retina, or structural abnormalities on OCT, were found. The RSF grafts were appropriately located at the posterior sclera and enclosed in fibrous capsules. The scleral thickness and collagen fiber content of the treated eyes increased after surgery. The ultimate stress of the reinforced sclera increased by 30.7%, and the elastic modulus increased by 33.0% compared to those of the control eyes at 6 months after surgery. Conclusion: Robust RSF hydrogels exhibited good biocompatibility and promoted the formation of fibrous capsules at the posterior sclera in vivo. The biomechanical properties of the reinforced sclera were strengthened. These findings suggest that RSF hydrogel is a potential material for PSR.